Embedding research into the organisational structure of smaller rural hospitals: building research culture and capacity and understanding perceived rural health workforce benefit - Laura Alston; Dai Pu; Sarah Wood; Michael Field; Hannah Beks; Olivia A. King; Nikita Wheaton; Catherine E. Huggins; Anna Wong Shee; Kevin Mc Namara; Vincent L. Versace (BMC Health Services Research)
Abstract Background Rural hospitals in Australia have not been afforded the same opportunities for research activity as their metropolitan counterparts. Equitable access to career and research opportunities has been identified as a potential strategy to enhance workforce satisfaction and retention in rural areas. Smaller rural hospitals show potential in being key settings for research; but minimal investment has translated into a lack of action and knowledge. Practical examples of how this can be done from an organisational structure point of view, are limited in the literature. Methods This cross-sectional study was undertaken in a rural hospital that services rural communities classed as MM4-5 by the Modified Monash Model. The study utilised the validated Research Capacity and Culture (RCC) tool to assess the impact of a rural hospital research unit on building research capacity and culture. It also explored the association between job satisfaction and research activity among hospital staff. Data analysis included descriptive statistics and linear regression. Results Seventy-four staff members completed the survey, with 15 reporting that they had worked with the research unit to complete projects. Among staff who received support from the Research Unit, there were higher RCC scores for 9 out of 20 organisational-level items. Rural hospitals staff rated the benefit of having research opportunities available (mean rating 7 out of 10) in their workplace for future career prospects. Conclusions This study provides evidence that the presence of a research unit, as part of the organisational structure, may assist in improving research capacity and culture within the rural hospital setting. It also identified areas for improvement in this context, as scores were not increased across all of the RCC domains and is an area of future development. Rural hospitals staff perceive the availability of a local research unit and research opportunitiestobebeneficialfortheircareer and this has implications for rural health workforce development strategies.